Phage Endolysin LysP108 Showed Promising Antibacterial Potential Against Methicillin-resistant Staphylococcus aureus - Lu, Yifei; Wang, Yingran; Wang, Jing; Zhao, Yan; Zhong, Qiu; Li, Gang; Fu, Zhifeng; Lu, Shuguang (Frontiers in Cellular and Infection Microbiology, 2021)
As a potential antibacterial agent, endolysin can directly lyse Gram-positive bacteria from the outside and does not lead to drug resistance. Considering that XN108 is the first reported methicillin-resistant Staphylococcus aureus (MRSA) strain in mainland China with a vancomycin MIC that exceeds 8 µg mL-1, we conducted a systematic study on its phage-encoded endolysin LysP108. Standard plate counting method revealed that LysP108 could lyse S. aureus and Pseudomonas aeruginosa with damaged outer membrane, resulting in a significant reduction in the number of live bacteria. Scanning electron microscopy results showed that S. aureus cells could be lysed directly from the outside by LysP108. Live/dead bacteria staining results indicated that LysP108 possessed strong bactericidal ability, with an anti-bacterial rate of approximately 90%. Crystal violet staining results implied that LysP108 could also inhibit and destroy bacterial biofilms. In vivo animal experiments suggested that the area of subcutaneous abscess of mice infected with MRSA was significantly reduced after the combined injection of LysP108 and vancomycin in comparison with monotherapy. The synergistic antibacterial effects of LysP108 and vancomycin were confirmed. Therefore, the present data strongly support the idea that endolysin LysP108 exhibits promising antibacterial potential to be used as a candidate for the treatment of infections caused by MRSA.